2008
DOI: 10.1093/pcp/pcn192
|View full text |Cite
|
Sign up to set email alerts
|

52Fe Translocation in Barley as Monitored by a Positron-Emitting Tracer Imaging System (PETIS): Evidence for the Direct Translocation of Fe from Roots to Young Leaves via Phloem

Abstract: The real-time translocation of iron (Fe) in barley (Hordeum vulgare L. cv. Ehimehadaka no. 1) was visualized using the positron-emitting tracer 52Fe and a positron-emitting tracer imaging system (PETIS). PETIS allowed us to monitor Fe translocation in barley non-destructively under various conditions. In all cases, 52Fe first accumulated at the basal part of the shoot, suggesting that this region may play an important role in Fe distribution in graminaceous plants. Fe-deficient barley showed greater translocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 54 publications
0
78
0
1
Order By: Relevance
“…Intervascular transfer is also required for other minerals to be selectively delivered to the grains. For example, redirection at the node from the xylem stream to newly developing organs, apical meristems, young leaves, or inflorescences, independent of the transpiration stream, has been observed for Zn (Obata and Kitagishi, 1980a, 1980b), Fe (Tsukamoto et al, 2009), and Cd (Kashiwagi et al, 2009). However, the transporters involved in these processes have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Intervascular transfer is also required for other minerals to be selectively delivered to the grains. For example, redirection at the node from the xylem stream to newly developing organs, apical meristems, young leaves, or inflorescences, independent of the transpiration stream, has been observed for Zn (Obata and Kitagishi, 1980a, 1980b), Fe (Tsukamoto et al, 2009), and Cd (Kashiwagi et al, 2009). However, the transporters involved in these processes have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Especially during the development of leaves, flowers, and seeds, these young organs act as sinks, and the requirement for phloem transport of micronutrients to these sinks is high. A recent study provided evidence that young leaves of barley (Hordeum vulgare) receive Fe primarily from the phloem, while older leaves receive Fe from the xylem (Tsukamoto et al, 2009). The conclusion that sink organs rely on a NA-dependent phloem pathway for obtaining adequate levels of Fe is supported by our finding that Fe accumulated in the phloem in the absence of NA.…”
Section: Na Functions In the Translocation Of Fe To Sink Organs Involmentioning
confidence: 99%
“…Generally, NA is needed for the unloading process and remobilization of Fe from the phloem in A. thaliana, which is especially important in the sink organs. In graminaceous species like barley, the situation might be different, and NA and phytosiderophores might be more generally involved in long-distance transport (Tsukamoto et al, 2009;Nishiyama et al, 2012).…”
Section: Na Functions In the Translocation Of Fe To Sink Organs Involmentioning
confidence: 99%
“…The mechanisms of iron transport in plants, once taken up by the roots, are less clear. It has recently been suggested that younger leaves receive their iron primarily from the phloem whereas older leaves receive iron from the xylem (Tsukamoto et al 2009). In the xylem iron is transported as Fe(III)-citrate (Tiffin 1966), in the phloem as Fe(III)-ITP (Iron Transporter Protein) or Fe-nicotianamine (NA) (Kruger et al 2002;Curie et al 2009).…”
Section: Introductionmentioning
confidence: 99%